Epistemology of Islamic Education According to Hasyim Asy'ari Thought - Ainuri, Ahmad; Wijaya, Mirza (UIN Raden Mas Said Surakarta, 2021)
This paper examines the epistemology of Hasyim Asy'ari as one of the Islamic scholars who has contributed to the development of Islamic education in Indonesia. This research is considered very important because previous studies of researchers only examine Islamic education and Morals. Thus, efforts to conduct philosophical studies related to epistemology use and seek its relevance in Indonesia. This study uses qualitative research with a rationalistic philosophical approach. Meanwhile, data analysis methods use content analysis. The study's findings showed that epistemology colored the thinking of Hasyim Asy'ari, among others: Bayani, Burhani, Irfani, and Authoritarianism. While paradigm Hasyim Asy'ari belongs to the Conservative-Religious tradition.